A Study on Teacher Talk Used to Male and Female Indonesian EFL Students - Putri Almira Fauziyyah Rachmayani; Setyo Wati; Pipit Prihartanti Suharto (Journal of Applied Linguistics (ALTICS), 2024)
The aim of this study was to examine how female teachers interacted with their male and female students in the classroom and to provide examples of how various patterns of classroom interaction could be used. The research method used in this research was qualitative-case study. Techniques of collecting data used in this research were observation, interview and video recording. In analyzing the data, the researcher applied three steps namely data display, data reductions, and data conclusion. The findings of this study revealed that: the teacher preferred to utilize particular patterns of the teacher talk to her male and female students, such as the use of praising or encouraging category that the teacher applied towards male students in order to encourage them during the lesson; the asking question category was the most dominant the teacher used towards the female students through call out students’ name and ask the questions that related to the topic lesson, meanwhile the males was called out their name and was asked the simple question.